PRESERVATION OF PALANG-PINTU ORAL LITERATURE: THROUGH LOCAL WISDOM BASED ON CREATIVE INDUSTRIES IN THE TIDUNG ISLAND COMMUNITY - Siti Gomo Attas; Gres Grasia Azmin; Marwiah Marwiah (University of Kuningan, 2023)
This study aims to find out how the conservation of oral literature through local wisdom based on creative industries in the Tidung Island community. The method used in this study is ethnography with observation, interview, and document techniques. The theory of performance structure by Koster as the theory used in this study, the value of local wisdom with the concept of John M. Echol and Hasan Syadily which is in accordance with the local wisdom of the people of Tidung Island, and the creative industry by Sariono in the show in the form of creative work of the people of Tidung Island. The results of this study: (1) the performance structure of Palang Pintu on Tidung Island in 2022, (2) The value of Islamic local wisdom in the Palang Pintu performance in the Tidung Island community, and (3) The creative industry of the Palang Pintu show on Tidung Island which was developed through a collaborative performance between Mandar silat as a local culture of the Tidung Island community by creating Betawi rhymes that are in accordance with the language and oral literary value on the Tidung Island.Keywords: conservation; creative industry; local wisdom; Palang Pintu; Tidung Island